Story of a Love Affair - Cronaca di un amore - Michaelangelo Antonioni (1950)
Paola is a young, beautiful woman married to a wealthy entrepreneur. She meets her former lover Guido after seven years, but their relationship is marked by tragic events.
Keywords: Crime, Drama, Romance